2022
DOI: 10.7759/cureus.26208
|View full text |Cite
|
Sign up to set email alerts
|

Hemothorax With White-Out Lung After Intrapleural Tissue Plasminogen Activator and Deoxyribonuclease Therapy in a Patient With Complicated Parapneumonic Effusion

Abstract: Tissue plasminogen activator (tPA) and recombinant deoxyribonuclease (DNase ) are used in treating pleural infection due to their mucolytic activity by effectively reducing pleural fluid viscosity. The combination of tPA and DNase has attracted considerable interest as an alternative to surgical intervention for treating complicated parapneumonic effusion in high-risk patients who are not good candidates for surgery. However, intrapleural hemorrhage has been reported as a villainous outcome in a few cases whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 8 publications
(26 reference statements)
0
2
0
Order By: Relevance
“…In June 2022, Mainali et al reported a case of a 57-year-old female with a large right exudative effusion complicated with parapneumonic effusion treated with t-PA and DNAse therapy leading to the formation of hemothorax on the first treatment with t-PA [16]. On the other hand, our patient showed a positive response to treatment to t-PA and DNAse.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…In June 2022, Mainali et al reported a case of a 57-year-old female with a large right exudative effusion complicated with parapneumonic effusion treated with t-PA and DNAse therapy leading to the formation of hemothorax on the first treatment with t-PA [16]. On the other hand, our patient showed a positive response to treatment to t-PA and DNAse.…”
Section: Discussionmentioning
confidence: 51%
“…Urinalysis was positive for protein (>500), esterase (trace), WBC (10)(11)(12)(13)(14)(15)(16)(17)(18)(19), WBC clumps, and red blood cells (30-49). Urine Legionella and Streptococcus pneumoniae antigens were negative.…”
Section: Case Presentationmentioning
confidence: 99%